2009
DOI: 10.3324/haematol.2009.015123
|View full text |Cite
|
Sign up to set email alerts
|

Myelin protein zero is naturally processed in the B cells of monoclonal gammopathy of undetermined significance of immunoglobulin M isotype: aberrant triggering of a patient's T cells

Abstract: BackgroundMonoclonal gammopathy of undetermined significance of immunoglobulin M isotype is a condition with clonally expanded B cells, recently suggested to have an infectious origin. This monoclonal gammopathy is frequently associated with polyneuropathy and antibodies against myelin protein zero, whereas the role of the T cells remains largely unknown. We analyzed protein zero-specific B cells, as antigen-presenting cells, and their capacity to activate T helper cells. Design and MethodsWe used a well-chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The maximum fold increase was observed in Ceramide antibody followed by TNF-α, followed by S100 antibody and PGL-1 (Table 1 and Figure 2 ) suggesting the combination of these four serological markers could be a choice to understand reaction and their relationship to nerve damage. In addition, to the above mentioned four serological markers other inflammatory and autoimmune markers which have a fold increase such as Interferon-inducible protein-10 (IP-10) [ 22 ] and Myelin P0 [ 23 - 25 ] should be explored for understanding the nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum fold increase was observed in Ceramide antibody followed by TNF-α, followed by S100 antibody and PGL-1 (Table 1 and Figure 2 ) suggesting the combination of these four serological markers could be a choice to understand reaction and their relationship to nerve damage. In addition, to the above mentioned four serological markers other inflammatory and autoimmune markers which have a fold increase such as Interferon-inducible protein-10 (IP-10) [ 22 ] and Myelin P0 [ 23 - 25 ] should be explored for understanding the nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of myelin P0 are associated with congenital hypomyelination, Dejerine-Sottas syndrome and Charcot-Marie-Tooth disease 2 [33]. Hellqvist et al (2010) [34] reported that myelin P0 was naturally processed in B cells in monoclonal gammopathy casting a new light on the important role of autoreactive myelin P0-specific B cells in the induction of the pathogenic T-cell responses observed in nerve lesions of patients. Future work to characterize epitope fine specificities of auto antibodies could identify the clinically significant regions involved in the pathogenesis of nerve damage.…”
Section: Discussionmentioning
confidence: 98%
“…17 MGUS with peripheral neuropathy reported that synthetic protein zero peptide-pulsed B cells significantly induced interleukin (IL)-2 secretion from autologous T cells compared with control antigen-pulsed cells. 18 Furthermore, the median IL-6 and IL-10 serum concentrations differed between patients with anti-MAG neuropathy or IgM-type PAN compared with healthy and neuropathy controls. 19 Another study reported that the attachment of human lymphocytes to IL-1β-activated bovine endoneurial microvascular endothelial cells was affected by the presence or absence of sulfoglucuronosyl paragloboside with HNK-1 epitopes on microvascular endothelial cells, so results strongly supporting the concept that immunological insults against bovine microvascular endothelial cells induce the destruction or malfunction of the blood-nerve barrier (BNB), resulting in the penetration of immunoglobulin molecules and attack of the peripheral nerve parenchyma.…”
Section: Pathological Findings and Pathophysiologymentioning
confidence: 95%
“…antibodies, and various cytokines and complement factors are involved in anti-MAG neuropathy. The putative pathophysiology of anti-MAG neuropathy is shown in Figure2 15,[18][19][20][21][22][23][24][25]. 2.2.5 | Current treatmentsRituximabAlthough there is no established anti-MAG neuropathy treatment at present, combining the results of the two randomized controlled trials, rituximab appeared to improve the disability and subjective impressions of change 26.…”
mentioning
confidence: 99%